“Dusk can be a magical time in the French Quarter”: Richard Ford’s New Orleans before and after Katrina in “Puppy” and “Leaving for Kenosha” - Gérald PRÉHER (E-REA)
Richard Ford has often claimed that he does not consider himself a Southern writer despite being born and raised in Mississippi. Apart from his first two novels, most of his works are set in the North (sometimes the Far North) but, since he lived in New Orleans for some time and knows the city very well, he has devoted two short stories to that singular city. In “Puppy” (2001) and “Leaving for Kenosha” (2008), Ford makes use of various clichés associated with the city; the characters’ behavior is also justified by their living there—space and self being intimately related. Focusing on the description of the city in the two stories, this article points out the gap between the flamboyant city of the past and its present ruins since the 2005 hurricane Katrina. Both stories rely on the dysfunction brought about by an intruder and as the narratives come to an end, some kind of balance has been restored because the life of the city takes over.